Classification of Agriculture Area for Materials Flow Analysis based on Digital Image Processing - Juntakut, Pongpun; Jantakat, Yaowaret; Ertel, Juergen (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2008)
-